2008
DOI: 10.1159/000151596
|View full text |Cite
|
Sign up to set email alerts
|

No Association between T222P/LGR8 Mutation and Cryptorchidism in the Moroccan Population

Abstract: Background: Cryptorchidism is the most common genital anomaly in men. The INSL3/LGR8 system is involved in testicular descent via gubernacular development. INSL3 binds with high affinity to its receptor LGR8 and receptor activation is associated with cAMP signaling. Analysis of human INSL3 and LGR8 mutations confirms that some cases of cryptorchidism are caused by mutations in these genes. The T222P mutation is the only one within the LGR8 gene associated with the cryptorchidism phenotype. A strong association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…The chromosome complement was determined by examining 40–50 metaphases from each patient. The SRY, NR5A1, GATA4, FOG2, INSL3, LGR8 and MAP3K1 genes were sequenced as previously described [2025] in all patients with DSD until the genetic diagnosis was determined (except in case 24, for which the brother, case 16, had been sequenced). In the patients with anorchia, the complete open reading frames of SRY, NR5A1, INSL3, MAMLD1 and the T222P variant for LGR8 were sequenced as previously described [2025].…”
Section: Methodsmentioning
confidence: 99%
“…The chromosome complement was determined by examining 40–50 metaphases from each patient. The SRY, NR5A1, GATA4, FOG2, INSL3, LGR8 and MAP3K1 genes were sequenced as previously described [2025] in all patients with DSD until the genetic diagnosis was determined (except in case 24, for which the brother, case 16, had been sequenced). In the patients with anorchia, the complete open reading frames of SRY, NR5A1, INSL3, MAMLD1 and the T222P variant for LGR8 were sequenced as previously described [2025].…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of this variant shows marked geographic differences, and it is mainly present in the Mediterranean area due to a "founder effect". [37][38][39][40] Given that this variant has been reported also in controls with normal testis descent (1-2%), it cannot be considered a clear-cut cause of cryptorchidism and should not be included in the list of causative genetic alterations of this disease. In Italy it seems to confer a mild risk to cryptorchidism but its diagnostic role is greatly limited by the fact that 1.7% of controls are carrier of this variant.…”
Section: Varicocelementioning
confidence: 99%
“…, 2003). However, a very recent Moroccan study has found this mutation also in non‐cryptorchid controls, suggesting that the phenotype is dependent on the genetic and/or environmental background (El Houate et al. , 2008).…”
Section: Pathophysiological Conditions With Abnormal Insl3 Levelsmentioning
confidence: 99%